Peranakan Chinese’s Literature in Doenia Baroe Magazine (1930) - Risa Junita Sari; Wannofri Samry; Yudhi Andoni (Lembaga Penelitian dan Pengabdian Universitas Andalas, 2020)
Doenia Baroe Magazine (1930) is a press media of Peranakan Chinese that contains a lot of literature from various genre. The purpose of this study is to explain themes, forms and orientation of Peranakan Chinese’s literature, so that might explain author’s idea of literary works.Literature from Doenia Baroe Magazine has become the overview of history of literature that written by Peranakan Chinese that use historical methodology. Chinese literature in Doenia Baroe Magazine are influenced by the identity tendency as Chinese people which brings out rendering literary works. Literature from Doenia Baroe Magazine are adaptive to the modernity of colonial environment without needed to remove their ancestral heritage. Literary works in Doenia Baru Magazine has various genres such as short story, feuilleton and poem that implicitly show the author’s new world. Peranakan Chinese’s literature has not just become the social reflection but also implies political identity of the era.The result of this study, the beginning of chinese’s literature is relevant with mentality of the era that affects the author’s idea.